Cranial osteology and taxonomy of albatrosses of genus Dimedea linneaus, 1758 and Thalassarche reichenbach, 1853 (procellariformes: Diomeidae) - Francisco V. Dénes; Luís Fábio Silveira (Papéis Avulsos de Zoologia, 2007)
The currently accepted albatross taxonomy, based on characters of external morphology, plumage patterns, tail shape, bill size and coloration, organization of the plates of the bill, and, more recently, molecular data such as cytochrome-b gene sequences, resulted in a division of the family Diomedeidae into four genera: Diomedea, comprising the great albatrosses; Phoebastria, the North Pacific albatrosses; Thalassarche, the mollymawks; and Phoebetria, the sooty mollymawks. However, there are only a few, old studies on albatross osteology, which focused mostly on supra-generic relationships. Research on the group's taxonomy and anatomy is important in order to establish a secure basis for the identification of each species, including the differences between males, females and specimens of different ages, and also to verify anatomic characters which might be found useful for phylogenetic analysis based on morphological markers. In the present study, 63 skulls of Diomedea and Thalassarche albatrosses were analyzed and compared, thus establishing topographic correspondences and determining primary homologies, these resulting in: (a) the finding of no pattern of anatomical variation related to sex and age for both T. melanophris and for T. chlororhynchos; (b) the assessment of eight cranial landmarks separating the genera Diomedea and Thalassarche; (c) the recognition of 13 cranial landmarks differing among T. melanophris, T. chlororhynchos and T. cauta; (d) the re-identification of several specimens based on skull characters. The characters here presented for the genera and species, along with further anatomical research on the skull of the Diomedeidae, including the genera Phoebetria and Phoebastria, may help to enlighten relationships within the family. A atual taxonomia dos albatrozes consiste na divisão da família Diomedeidae em quatro gêneros: Diomedea, que inclui os grandes albatrozes; Phoebastria, formado pelos albatrozes do norte do Pacífico; Thalassarche, para os chamados "mollymawks" e Phoebetria, para os "mollymawks fuliginosos" e foi baseada em caracteres da morfologia externa, padrões de plumagem, forma da cauda, tamanho e coloração do bico e a organização das placas da ranfoteca e, mais recentemente, seqüências do citocromo-b. Entretanto, existem poucos e antigos estudos sobre a osteologia dos albatrozes que estudaram apenas as relações supra-genéricas. A pesquisa na taxonomia e na anatomia do grupo é importante para se criar uma base segura para a identificação das espécies, incluindo aí as diferenças existentes entre machos, fêmeas e de exemplares em diferentes idades, além de se verificar caracteres anatômicos cranianos que podem revelar-se úteis para análises filogenéticas com base em marcadores morfológicos. No presente trabalho, 63 crânios de representantes dos gêneros Diomedea e Thalassarche foram analisados e comparados, estabelecendo correspondências topográficas e determinando homologias primárias, o que resultou em: (a) a descoberta da ausência de padrões de distinção anatômica relacionados ao sexo e à idade para T. melanophris e para T. chlororhynchos; (b) levantamento de oito caracteres do crânio que separam os gêneros Diomedea e Thalassarche; (c) reconhecimento de 13 caracteres cranianos que diferem entre T. melanophris, T. chlororhynchos e T. cauta; (d) re-identificação de vários espécimes baseados em caracteres cranianos. Os caracteres aqui apresentados para os gêneros e espécies, juntamente com futuras pesquisas na anatomia do crânio de Diomedeidae, incluindo os gêneros Phoebetria e Phoebastria, podem ajudar na elucidação das relações de parentesco dentro da família.